KEMAMPUAN BEBERAPA JAMUR TANAH DALAM MENGURAIKAN PESTISIDA DELTAMETRIN DAN SENYAWA LIGNOSELULOSA - YB. Subowo (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Some of soil fungi capable in degrading pesticide deltamethrin, therefore they can be used as fertilizer in organic farming. As a biofertilizer ,fungus also must be able to provide nutrients for plants. The purpose of the study was to obtain fungal isolates that have the ability to decompose pesticides deltamethrin and lignocellulose compounds, dissolved inorganic phosphate compounds and produce growth hormone IAA (Indole Acetic Acid) . The fungal isolates will then be used in the manufacture of bio-fertilizers. Soil samples were put into mineral medium containing deltamethrin, fungus that grew on this medium would then be isolated. The ability of fungus in decomposing deltamethrin was observed using GC. While the ability of fungi to decompose lignocellulose, to dissolve inorganic phosphate compounds and to produce IAA was observed using a spectrophotometer. The results showed that the fungus Aspergillus niger TR1 had the ability to degrade 90.68% of deltamethrin 500 ppm after 1 h incubation and to degrade 0.46% of Poly R - 478 by after 30 min incubation. In addition, this fungus had cellulase activity of 0.029 units/ml and were able to dissolve inorganic phosphate compounds and produce IAA.